Suicide and grief: quantitative analysis of brazilian publications on Twitter - Pedrollo,Laysa Fernanda Silva (2021)
Abstract Background: The approach of suicide and suicide grief in online environments is a reality that goes along with technological advances. Used by their users as spaces for expression, social networks are increasingly being a unique source of information for researchers. In this scenario, Twitter establishes itself as an important object of analysis for understanding the experience on the social network with emphasis on approaches in relation to the themes of suicide and grief, in order to reflect the impacts and implications for the mental health of its users. Aim: Analyze the publications of Brazilian public profiles related to thematic of suicide and grief on social network Twitter. Methods: Retrospective, documentary research with a quantitative approach that analyzed 1.645 Brazilian publications on Twitter using descriptive statistics, association tests and Multiple Logistic Regression Analysis. Results: Publications addressing famous people without comments, shares, or likes predominated. Profiles that expressed suicidal behavior on Twitter were more likely to feature pro-suicidal content in their publications. Conclusions: Twitter is a social network used by its users to discuss suicide and grief, however, with little approach to questions about suicide prevention and prevention. The network stands out for its unique characteristics, on the part of its users and the usability provided, which allows the publication of content and interactions on these topics in a varied and little investigated ways.